Experience of post-traumatic growth among parents of children with biliary atresia undergoing living-related liver transplantation: a descriptive phenomenological study - ZhiRu Li; FangYan Lu; Li Dong; Li Zheng; JingYun Wu; SiYuan Wu; Yan Wang; HuaFen Wang (European Journal of Psychotraumatology)
Objectives: To explore the experience of post-traumatic growth among parents of children with biliary atresia undergoing living-related liver transplantation.Methods: Participants were recruited within 2 weeks of their child's transplant surgery using purposive sampling. Transcripts were analyzed using Colaizzi's descriptive analysis framework, with collaborative analysis conducted using NVivo 12 software and a post-traumatic growth model.Results: Five themes were identified: (a) experiencing a devastating blow, (b) cognitive reconstruction under overwhelming pain, (c) an arduous journey of decision-making, (d) rebirth in adversity and (e) post-traumatic growth. Parents undergo significant post-traumatic responses to their child's diagnosis of biliary atresia and liver transplantation, marking two major traumatic events. During the diagnostic stage, parents experience intense post-traumatic reactions characterized by emotional fluctuations and intrusive thoughts. The early treatment phase represents a crucial time for parents to transition from `denial of reality' to `accepting diseases'. The process of liver transplantation is also a significant traumatic event, accompanied by a final hope. Parents in the stable period after liver transplantation feel fortunate, hopeful and grateful, and their post-traumatic growth manifests gradually.Conclusions: Parents' experience of post-traumatic growth involves dynamic changes. Tailored intervention strategies should be developed for different stages to enhance their post-traumatic growth and psychological well-being. During the early treatment stage, mental health professionals could provide cognitive interventions to encourage parents to express their negative emotions and guide them to develop positive cognition toward traumatic events. The coping strategies and increasing personal growth are also important. In the postoperative stage, mental health professionals need to fully evaluate the coping styles of parents, and encourage them to establish effective internal coping strategies, while classic gratitude interventions could be given during the post-traumatic growth stage. Future research could involve a longitudinal qualitative study to explore parents' post-traumatic growth experiences at different stages of their children's transplantation process.